Comparing different approaches to tackle the challenges of global carbon pricing - Eddy Bekkers; Gianmarco Cariola (World Trade Organization (WTO), 2022)
Climate change mitigation faces two main policy challenges: the need for global cooperation to tackle the collective action problem and the need to share the burden of global carbon pricing fair way following the principle of common but differentiated responsibility (CBRD). In this paper we explore the best ways to incentivize regions to reduce their CO2 emissions while minimizing the welfare losses for low-income countries using simulations with a recursive dynamic computable general equilibrium (CGE) model. We first present the necessity, efficiency and urgency of global carbon pricing policies climate change mitigation policies. Global carbon pricing is necessary to tackle climate change, is more efficient than regional carbon pricing, and is urgent to prevent a patchwork of carbon pricing policies leading to calls for border carbon adjustment (BCA). However, because the impact of global carbon pricing on most regions is negative, complementary policies are needed to provide sufficient incentives to join a global carbon pricing coalition and at the same time share the burden fairly. We examine four potential complementary policies: BCA, Nordhaus's climate club, a global incentive scheme, and emission trading with progressive emission reduction targets. We evaluate these proposals based on their projected effects on average income and income inequality among countries, as well as their effectiveness as an incentive to introduce carbon pricing. BCA scores poorly along the three dimensions; Nordhaus's carbon club performs well as an incentive tool but has a negative impact on income and income inequality; the global carbon incentive has a positive impact on income and income inequality but performs poorly as an incentive tool; and emission trading with progressive reduction targets scores well across all dimensions. We conclude with a discussion of the feasibility of emission trading.
Keywords: F15; F62; F63; 330; structural change; international trade; globalization